PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 010 SEMELINANG DARAT KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU - Surtini Surtini; Gustimal Witri; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrac : This research is a classroom action research that aims to improve the learning outcomes of fourth grade elementary school IPA siswa 010 Semelinang Darat Kecamatan Peranap of Indragiri Hulu through the application of guided inquiry learning model. This research was conducted on March 9, 2015 until April 6, 2015. The subjects were fourth grade students of SD Negeri 010 Semelinang Army totaling 30 people comprising 13 men and 17 women. This study aims to determine the thoroughness of science student learning outcomes in improving the quality of science teaching by guided inquiry learning model application. This thesis presents the results of student learning gained through daily test I in the first cycle and the second daily test on the second cycle. In the first cycle of learning outcomes 69.33 on the second cycle student learning outcomes on average 75.17. So the increase in the average student at 8,42. From these results are not achieved KKM students at the first cycle were 17 students and 8 students in the second cycle. Students who complete the first cycle of 22 people, the second cycle of 27 people. Mastery learning of individuals in the first cycle, there are 22 people and 73.33% classical completeness, the second cycle there are 27 people with classical completeness 90.00%. The average activity of teachers in the first cycle was 67.86% with the category enough, on the second cycle was 89.29% with the good category. The average activity of students in the first cycle was 71.43% with the good category, the second cycle was 91.08% From this study it can be concluded that the implementation of inquiry learning model can improve learning outcomes IPA on fourth grade students of SD Negeri 010 Semelinang the District Land Peranap school year 2014/2015. Keywords: Guided Inquiry learning, learning outcomes.